MicroRNA‐466a‐3p attenuates allergic nasal inflammation in mice by targeting GATA3. (30th June 2019) - Chen, Z.; Deng, Y.; Li, F.; Xiao, B.; Zhou, X.; Tao, Z.
Summary: Allergic rhinitis is thought to be an allergic disease associated with immunoglobulin (Ig)E‐mediated immune response, characterized by increased T helper type 2 (Th2) cytokine production, elevated eosinophil levels in the nasal mucosa and induced nasal secretions. MicroRNA (miRNA) microarray data revealed that the expression level of miR‐466a‐3p was significantly decreased. Notably, GATA binding protein (GATA‐3) was identified as one of its target genes through miRNA target prediction web tools. The expression levels of miR‐466a‐3p were altered by mimics and lentivirus both in vivo and in vitro, similar to those of GATA‐3. Furthermore, the symptoms and histology of allergic rhinitis as well as the levels of serum IgE and interleukin (IL)‐4 were examined in different groups of mice. Interestingly, the results for lentiviral miR‐466a‐3p‐treated allergic rhinitis mice were relatively similar to normal mice, compared to allergic rhinitis mice without treatment. Also, miR‐466a‐3p negatively regulated GATA‐3 expression in allergic rhinitis mice, indicating the participant of Th2‐cell responses in allergic rhinitis. Taken together, our findings highlight a new perspective on the role of miR‐466a‐3p in allergic rhinitis. In addition, this study provides a theoretical framework and experimental reference for future research targeting microRNAs as therapeutic targets and diagnostic biomarkers of allergic rhinitis. Abstract : Allergic rhinitis is thought to be an allergic disease associated with IgE‐mediated immune response, characterized by increased Th2 cytokine production, elevated eosinophil levels in the nasal mucosa and induced nasal secretions. MicroRNA microarray data revealed that the expression level of miR‐466a‐3p was significantly decreased. The results for lentiviral miR‐466a‐3p‐treated allergic rhinitis mice were relatively similar to normal mice, compared to allergic rhinitis mice without treatment. Besides, miR‐466a‐3p negatively regulated GATA3 expression in allergic rhinitis mice, indicating the participant of Th2‐cell responses in allergic rhinitis. Our findings highlight a new perspective on the role of miR‐466a‐3p in allergic rhinitis.